1984
DOI: 10.1007/bf00582594
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubular HCO 3 − , H+ and fluid transport during maleate-induced acidification defect

Abstract: The mechanism of tubular acidification was studied in proximal tubular acidification defect induced in rats by acute parenteral infusion of maleate (200 mg/kg), which causes diuresis and bicarbonaturia. Proximal tubular bicarbonate reabsorption and H+ ion secretion were determined by stopped-flow microperfusion and measurement of luminal pH by Sb microelectrodes. Stationary pH increased in proximal tubule from 6.78 to 7.25 and bicarbonate reabsorption decreased from 1.32 to 0.51 nmol/cm2 X s. In these segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The aforementioned damages to the proximal renal tubules of the kidney, collectively known as Fanconi syndrome, can result in cell necrosis and renal tubular injury in the proximal tubules (Bunton, Fuller, Perry, & Shiner, ). With the mechanisms still unclear, animal studies demonstrated that MA inhibit the activity of Na‐K‐ATPase, H‐ATPase and Na/H antiporter on columnar cells; these interferences disrupt the transport of sodium ions, bicarbonates, as well as the pH balance of the kidney (Eiamong, Spohn, Kurtzman, & Sabatini, ; Everett et al, ; Reboucas, Fernandes, Elias, de Mello‐Aires, & Malnic, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned damages to the proximal renal tubules of the kidney, collectively known as Fanconi syndrome, can result in cell necrosis and renal tubular injury in the proximal tubules (Bunton, Fuller, Perry, & Shiner, ). With the mechanisms still unclear, animal studies demonstrated that MA inhibit the activity of Na‐K‐ATPase, H‐ATPase and Na/H antiporter on columnar cells; these interferences disrupt the transport of sodium ions, bicarbonates, as well as the pH balance of the kidney (Eiamong, Spohn, Kurtzman, & Sabatini, ; Everett et al, ; Reboucas, Fernandes, Elias, de Mello‐Aires, & Malnic, ).…”
Section: Introductionmentioning
confidence: 99%
“…transport of sodium ions, bicarbonates, as well as the pH balance of the kidney (Eiamong, Spohn, Kurtzman, & Sabatini, 1995;Everett et al, 1993;Reboucas, Fernandes, Elias, de Mello-Aires, & Malnic, 1984).…”
mentioning
confidence: 99%
“…Using this method, it was possible to obtain evidence of a role of vacuolar H + -ATPase in the proximal tubule [32]; that in the proximal tubule adrenocortical hormones (aldosterone, corticosterone) support bicarbonate reabsorption [33]; that protein kinase C inhibits this transport, and that maleate causes a proximal tubule acidification defect [34]. More recently it was found that amphotericin B is responsible for a distal acidification defect which reduces the transepithelial pH gradient [31].…”
Section: In Vivo Micropuncture and Microperfusionmentioning
confidence: 99%